Exploring BeagleBone Tools and Techniques for Building with Embedded Linux - Molloy, Derek (Wiley, 2014)
guidance and online peer support help you transition from beginner to expert as you master the techniques presented in Exploring BeagleBone, the practical handbook for the popular computing platform